1998
DOI: 10.1046/j.1440-1819.1998.00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered adhesion efficiency and fibronectin content in fibroblasts from schizophrenic patients

Abstract: Cultured ®broblasts from the cutaneous tissue of 16 schizophrenic patients were compared with 16 control cultured ®broblasts from the healthy subjects. The ®broblasts from the schizophrenic patients showed a decreased adhesion ef®ciency within 30 min after plating compared to that of the control subjects. However, after 90 min, there was no signi®cant difference between the groups, where more than 90% of the cells from both groups had adhesed to the plate. By immunohistochemistry and western blotting using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Fibronectin is a high molecular weight ECM glycoprotein that binds to integrin receptors and plays important roles in neuro- and synaptogenesis. Dysregulation of fibronectin may result in neurodevelopmental abnormalities related to the pathogenesis of Sz [58, 59]. In contrast, a study showed no significant association of fibronectin with Sz [60].…”
Section: Changes In Brain Ecm In Neurodegenerative Conditionsmentioning
confidence: 99%
“…Fibronectin is a high molecular weight ECM glycoprotein that binds to integrin receptors and plays important roles in neuro- and synaptogenesis. Dysregulation of fibronectin may result in neurodevelopmental abnormalities related to the pathogenesis of Sz [58, 59]. In contrast, a study showed no significant association of fibronectin with Sz [60].…”
Section: Changes In Brain Ecm In Neurodegenerative Conditionsmentioning
confidence: 99%
“…Of paramount importance, the field requires pragmatic methods that can readily derive large numbers of relevant cells from multiple cases and controls, which are needed to represent the spectrum of variability between individuals. Accessible non-neural cells like skin fibroblasts or transformed lymphocytes have been used to identify differences in cell biology associated with schizophrenia (SZ) and Parkinson's disease (PD) (Mahadik and Mukherjee, 1996;Miyamae et al, 1998;WinklerStuck et al, 2004;Hoepken et al, 2008) but the utility of non-neural cells for understanding the cellular bases of neurological and neuropsychiatric disorders is limited (Matigian et al, 2008). Another approach is to develop stem cell models of disease: embryonic stem (ES) cells carrying genetic mutations have been isolated after pre-implantation genetic diagnosis (Verlinsky et al, 2005;Mateizel et al, 2006), and induced pluripotent stem (iPS) cells have been generated from patients, including those with PD (Park et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is not the only disease related to FAK dysregulation. Early reports pointed to decreased adhesion efficiency in fibroblasts of schizophrenic patients (Miyamae et al, 1998), although the localization and amount of FAK in these cells was not observed to change. Only recently it was demonstrated that focal adhesion dynamics and FAK expression are dysregulated in olfactory mucosa neurospheres obtained from schizophrenia patients (Fan et al, 2013).…”
Section: A Role For Fak In Neurological Diseasesmentioning
confidence: 82%